2004
DOI: 10.1159/000077841
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Effects of Naltrexone and Loratadine on Uremic Pruritus

Abstract: Background: Two recent studies have provided opposite results on the efficacy of naltrexone on uremic pruritus. We have performed a third study. Objective: To compare the efficacy and tolerance of naltrexone and loratadine in uremic pruritus. Patients/Methods: Among 296 hemodialyzed patients, 65 suffered from uremic pruritus. Fifty-two patients participated in the study. The patients were treated for 2 weeks with naltrexone (50 mg/day; 26 patients) or loratadine (10 mg/day; 26 patients), after a washout of 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…These studies yielded mixed results. [89][90][91] In a randomized, controlled, crossover study of 15 HD patients, 1 week of naltrexone treatment significantly improved pruritus severity compared to placebo. 49 Two subsequent trials, however, failed to confirm this effect.…”
Section: Opioid Imbalance Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies yielded mixed results. [89][90][91] In a randomized, controlled, crossover study of 15 HD patients, 1 week of naltrexone treatment significantly improved pruritus severity compared to placebo. 49 Two subsequent trials, however, failed to confirm this effect.…”
Section: Opioid Imbalance Treatmentmentioning
confidence: 99%
“…90 In another randomized trial, naltrexone did not significantly improve pruritus compared to loratidine over a 2-week treatment period. 91 Subsequently, peripheral kappa-opioid receptor agonists showed more promising results to treat CKD-aP. The most widely studied kappa-opioid receptor agonist is nalfurafine.…”
Section: Opioid Imbalance Treatmentmentioning
confidence: 99%
“…For itching intensity, we adapted two scales from those used most widely for quantifying intensity of pain: the 100-mm visual analog scale (VAS) (5-12) and the 11-point numerical rating scale (NRS) (13)(14)(15). The VAS scale already has been used for assessing itching intensity in clinical trials (5)(6)(7)(8)(9)(10)(11)(12). We were interested in comparing patients' ease of use of the NRS with the VAS and in measuring correlations between the two scales.…”
Section: Patient-reported Outcomes Instrument Developmentmentioning
confidence: 99%
“…While Peer et al [62] showed in a small placebo-controlled clinical trial that naltrexone, which is a μ-receptor antagonist, is effective, PauliMagnus et al [45] failed to demonstrate any efficacy of naltrexone in the treatment of uremic pruritus. Later, Legroux-Crespel et al [63] conducted a comparative study between naltrexone and loratadine, and concluded that naltrexone is not effective and not well-tolerated because of frequent side effects, except in a small subset of patients. More recently, another perspective was elaborated regarding the use of a қ-agonist, for қ-receptor stimulation inhibits μ-receptor effects both peripherally and centrally, and hence might inhibit itching induced by substance P. In line with this concept, Wikstrom et al [64] conducted two multicenter, randomized, double-blind, placebo-controlled studies that enrolled 144 patients with uremic pruritus to receive post-dialysis intravenous treatment with either nalfurafine, a novel қ-receptor agonist, or placebo for 2 to 4 weeks.…”
Section: Opioid Antagonistsmentioning
confidence: 99%